Mentoring the Implementation of Innovative Framework Curriculum for Non-Formal Institutions at the SAS ANA Group Foundation: Pendampingan Penerapan Kurikulum Kerangka Inovatif Untuk Lembaga Nonformal di Yayasan SAS ANA Group - Firmansyah, Firmansyah; Lubis, Asnarni; Lubis, Nazriani (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The partner is the SAS ANA Group Foundation, Partners are a Course Institution (non-formal education), and partners experience many fundamental problems, based on the results of interviews with the Head Tutor in the learning process so far there is no curriculum, implementation plans, textbooks, and fixed schedules that every tutor should have in carrying out learning interestingly. Partners will be given training and assistance on how to produce worksheets that are used using the CTL learning syntax, then collaborated with IoT-based assessments, so this assistance hopes to improve tutor abilities. The results obtained This service activity contributes to the IQF that must be implemented in LKP, by completing the IQF section of teaching materials, learning strategies, learning evaluations, and supporting activities tailored to partners' needs. There is an increase in the understanding of the IQF to be implemented in LKP, with data analysis using the Paired Sample Test it is known that the value obtained is sig 0.000, the condition for increasing understanding of the IQF is if the sig value is <0.05, in this case, it is clear that there is an increase in the implementation of activities dedication to the material understanding of IQF